Identidades Religiosas Brasileiras e seus Exclusivismos (Brazilian Religious Identities and their exclusiveness) - DOI: 10.5752/P.2175-5841.2011v9n23p782 - Wachholz, Wilhelm (Horizonte, 2011)
The Christianity which was introduced in the 16th century in Brazil affirmed itself in opposition to prior religions, showing traits of exclusiveness and intolerance. With these traits Christianity sought to denigrate the indigenous peoples, the new Christians and the Blacks by do not accepting them in their otherness. In the 19th century, with the introduction of Protestantism, and, in the 20th century, with the appearance of Pentecostalism and Neo-Pentecostalism, similar traits of mutual exclusiveness and negation can be verified in the intra-Christian realm. An analysis of the history of religions in Brazil shows that the religious identities were constructed through the dynamic of mutual negation. From this one can conclude that the identities of religions were not build in isolation but through the relations, sometimes marked by the dynamic of contrasts, differentiations and mutual stigmatizations. This is seen by the establishment of boundaries, which commonly are characterized by bipolar discourses, with the intent of producing exclusions by naming the other by unfaithful, atheist and heretical. The result can be verified by the anti-ecumenical characteristic of these religions.